Early non‐invasive ventilation treatment for respiratory failure due to severe community‐acquired pneumonia. (28th July 2014) - Nicolini, Antonello; Ferraioli, Gianluca; Ferrari‐Bravo, Maura; Barlascini, Cornelius; Santo, Mario; Ferrera, Lorenzo
Abstract: Background and Aims: Severe community‐acquired pneumonia (sCAP) have been as defined pneumonia requiring admission to the intensive care unit or carrying a high risk of death. Currently, the treatment of sCAP consists of antibiotic therapy and ventilator support. The use of invasive ventilation causes several complications as does admission to ICU. For this reason, non‐invasive ventilation (NIV) has been used for acute respiratory failure to avoid endotracheal intubation. However, few studies have currently assessed the usefulness of NIV in sCAP. Methods: We prospectively assessed 127 patients with sCAP and severe acute respiratory failure [oxygen arterial pressure/oxygen inspiratory fraction ratio (PaO2 /FiO2 ) <250]. We defined successful NIV as avoidance of intubation and the achievement of PaO2 /FiO2 >250 with spontaneous breathing. We assessed predictors of NIV failure and hospital mortality using univariate and multivariate analyses. Results: NIV failed in 32 patients (25.1%). Higher chest X‐ray score at admission, chest X‐ray worsening, and a lower PaO2 /FiO2 and higher alveolar‐arteriolar gradient (A‐aDO2 ) after 1 h of NIV all independently predicted NIV failure. Higher lactate dehydrogenase and confusion, elevated blood urea, respiratory rate, blood pressure plus age ≥65 years at admission, higher A‐aDO2, respiratory rate and lower PaO2 /FiO2 after 1 h of NIV and intubation rate were directly related to hospital mortality. Conclusions: Successful treatment is strongly related to less severe illness as well as to a good initial and sustained response to medical therapy and NIV treatment. Constant monitoring of these patients is mandatory.